Percepções do ambiente educacional: associações com níveis de estresse e resiliência na formação de estudantes de medicina - SUZIGAN, Erika Magalhães (2025)
This study is linked to research line 2: "Teacher Training and Action and Educational Practices" of the Postgraduate Program in Education at Unoeste. The medical course is known for presenting several stressors that may be linked to psychological conditions, environmental elements and other variables. Thus, this research had the general objective of investigating the relationships between students' perceptions of the educational environment and levels of stress and resilience in the medical course. To achieve this objective, four studies were developed. In the first, a scoping review was carried out on stress and resilience in medical training, with searches in the databases PubMed, Scielo Catalog of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel (CAPES), ERIC, Virtual Health Library (BVS) and Brazilian Digital Library of Theses and Dissertations (BDTD). After applying the inclusion and exclusion criteria, 23 articles were selected, with a predominance of observational studies. The second study aimed to seek associations between medical students' perceptions of the educational environment and sociodemographic and health variables. The research involved 135 participants, with an average age of 22.8 years. A sociodemographic questionnaire and the Dundee Ready Educational Environment Measure (DREEM), which assesses students' perception of the learning environment, were applied. The analyses revealed that there were statistically significant differences for the DREEM factor perception of results, with lower scores for students without scholarships and higher scores for students with scholarships. Participants who did not use psychotropic drugs had higher scores in all DREEM factors. Participants who did not practice physical activity had lower scores in perception of the environment. The third study aimed to analyze stress and resilience levels, seeking associations with explanatory variables related to these psychological conditions. The sample consisted of 135 medical students, 98 female (73.1%) and 36 male. For data collection, a sociodemographic questionnaire, the Perceived Stress Scale (PSS-10) and the Wagnild and Young Resilience Scale were applied. Regarding perceived stress, the results showed that younger people had higher scores than older people. Regarding resilience, students under 24 years old had lower scores than those over this age. People who do not practice physical activity had higher scores than people who practice physical activity on the stress scale, while people who do not practice physical activity had lower resilience scores. Finally, the fourth study verified the possible associations between the perception of the educational environment with stress and resilience levels; and sought to identify possible predictors of resilience and perceived stress. Using network analysis, it was shown that perception of academic results and perception of learning have a positive relationship with resilience; and that an academic environment, which enhances strategies that facilitate the perception of social relationships, perception of the educational environment/atmosphere and perception of learning, reduces stress levels.